2016
DOI: 10.1136/annrheumdis-2016-eular.5577
|View full text |Cite
|
Sign up to set email alerts
|

AB0621 From Vedoss To Established Systemic Sclerosis Diagnosis According To The New ACR/EULAR 2013 Classification Criteria: A French-Italian Capillaroscopic Survey

Abstract: BackgroundNailfoldCapillaroscopy (NC) is a diagnostic and sensitive tool in order to investigate Raynaud's phenomenon (RF) that is the hallmark of both Systemic Sclerosis (SSc) and Very Early Diagnosis Of ScS (VEDOSS) patients. Thus NC is largely used in patients with these conditions and NC specific abnormalities have become a minor criteria in ACR/EULAR SSc Criteria in 2013.ObjectivesAim of our study was to monitor NC changes in a group of 66 VEDOSS patients, enrolled in two EUSTAR center.MethodsWe selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Nailfold capillaroscopy is a non-invasive diagnostic tool in SSc, allowing clinicians to assess microvascular damage in early stages of the disease [ 10 ]. It is included in the latest classification criteria for SSc [ 11 ] as well as in the criteria for the very early diagnosis of SSc (VEDOSS) [ 12 ]. Recently, nailfold capillaroscopy has also emerged as a potential surrogate marker of SSc progression [ 13 ] as several studies have demonstrated that microvascular alterations might correlate with visceral organ involvement, particularly vascular complications such as PAH [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nailfold capillaroscopy is a non-invasive diagnostic tool in SSc, allowing clinicians to assess microvascular damage in early stages of the disease [ 10 ]. It is included in the latest classification criteria for SSc [ 11 ] as well as in the criteria for the very early diagnosis of SSc (VEDOSS) [ 12 ]. Recently, nailfold capillaroscopy has also emerged as a potential surrogate marker of SSc progression [ 13 ] as several studies have demonstrated that microvascular alterations might correlate with visceral organ involvement, particularly vascular complications such as PAH [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, RP with a positive ANA, puffy fingers and abnormal nailfold capillaroscopy that represents microcirculatory abnormalities, has a high predictive value for developing SSc. 8 However, while an SSc-pattern of nailfold videocapillaroscopy (NVC) is described, this pattern is also found in SLE. 9 In addition, in ANA positive individuals, autoantibodies to self-antigens that are not traditionally captured by current screening techniques reveal that SLE patients specifically display reactivity to many autoantigens.…”
Section: Clinical Assessment and Serum Tests In Sle-ssc Overlap With ...mentioning
confidence: 99%
“…Secondary Raynaud’s phenomenon (SRP) occurs in response to cold temperature or emotional stress, in the setting of underlying vascular disturbance, and is often associated with digital pain and ischemic ulcers [ 89 , 90 , 91 , 92 ]. However, it may occasionally lead to gangrene with tissue loss or the need for digital amputation [ 89 , 90 ].…”
Section: Peripheral Vascular Manifestationsmentioning
confidence: 99%